Left atrial reservoir strain may be a load independent index of diastolic dysfunction in liver cirrhosis patients. (4th February 2022) - Dimitroglou, Y; Aggeli, C; Alexopoulou, A; Alexopoulos, T; Patsourakos, D; Polytarchou, K; Kakiouzi, V; Tsartsalis, D; Valatsou, A; Kastellanos, S; Raftopoulos, L; Angelis, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Cirrhotic cardiomyopathy is characterized by high cardiac output, reduced peripheral resistance and diastolic dysfunction. Specifically, diastolic dysfunction has been correlated with the prognosis in liver cirrhotis patients independently of the disease severity. Left atrial reservoir strain (LASr) is a novel index which is inversely correlated with left ventricular end-diastolic pressure, but has not been adequately studied in cirrhotic patients. Purpose: To investigate the correlations between LASr and diastolic function or disease severity in cirrhotic patients. Methods: Echocardiographic analysis of 51 consecutive cirrhotic patients was performed and images were analyzed off-line. LASr was calculated semi-automatically using dedicated software and was feasible in 49 patients. Clinical and biochemical examination was used to assess severity of liver disease by calculating MELD-Na score. Results: Mean age was 58.0± 8.6 years, 37 (75.5%) were males, mean MELD-Na score was 15.6 ±7.5 and mean LASr was 39.7 ±12.5. LASr correlated with age (r=-0.415, p = 0.003), LAVI (r=-0.329, p = 0.022), e' (r = 0.476, p = 0.001), E/e (r=-0.401, p = 0.004) and GLS (r=-0.388, p = 0.006), but not with ejection fraction, stroke volume or MELD-Na score. MELD-Na score correlated with ejection fraction (r = 0.316, p = 0.029), stroke volume (r = 0.549, p < 0.001), left atrial volume index (r = 0.575, p < 0.001), GLS (r = 0.521, p < 0.001), right atrial end systolic area (r = 0.368, p = 0.011) and right ventricular diameter (r = 0.541, p < 0.001) reflecting high cardiac output state in patients with advanced cirrhosis. LASr was significantly lower in patients with E/e' >14 (22.5 ± 13.6) when compared to patients with E/e' 8-14 (37.3± 10.6, p = 0.039) and E/e'<8 (44.7± 12.0, p = 0.003). The two latter groups also differed significantly (p = 0.034). LASr correlation with E/e' was the only statistically significant correlation in a multiple regression model including left ventricular end diastolic volume, ejection fraction and left atrial volume (B=-1.371, P = 0.023). Correlation of LASr with MELD-Na score remained non-significant. Conclusion: LASr correlates inversely with E/e' ratio in liver cirrhotic patients, but does not correlate with load dependent echocardiographic parameters and disease severity. Hence in this special population, LASr may be an earlier and more specific index of diastolic dysfunction than traditional echocardiographic indices. Further studies are needed to examine the prognostic significance of LASr in cirrhotic patients.